(untitled) (Research, Society and Development, 2022)
This present work was aimed at evaluating the clinical knowledge of general practitioners (GP), attenting a specialization course on Endodontics in the cities of Recife - Brazil and João Pessoa - Brazil, as regards the endo-perio lesions, owing to the difficulties, noticed when stablishing their diagnosis and, therefore, when performing the therapeutic decision. On this purpose, a questionnaire with three case-reports, concerned with those lesions, was answered by a sample of 54 GPs. During the interviews, they were inquired on their possible diagnosis and treatment, by means of digitalized radiographies and case decriptions. The results revealed a great range of variation, even higher than what was expected, in reference to the diagnosis and proposed therapies, associated to a low frequency related to the right decision-making. In conclusion, the majority of the interviewed students does not retain the required scientific knowledge towards the studied subject.